GPX4 is a key ferroptosis regulator orchestrating T cells and CAR-T-cells sensitivity to ferroptosis - Marta Kłopotowska; Iwona Baranowska; Szymon Hajduk; Anna Jurga; Natalia Leśniowska; Michał Łaźniewski; Monika Granica; Marta Krawczyk; Milena Dziewicka; Agnieszka Graczyk; Jan Słupski; Radosław Zagożdżon; et al. (Cancer Immunology, Immunotherapy)
Abstract Induction of ferroptosis, an iron-dependent form of regulated cell death, holds promise as a strategy to overcome tumor resistance to conventional therapies and enhance immunotherapy responses. However, while the susceptibility of tumor cells to ferroptosis is extensively studied, limited data exists on the vulnerability of immune cells to disturbed iron balance and lipid peroxidation. Here, we found that T-cell stimulation rewires iron and redox homeostasis and by increasing levels of reactive oxygen species and labile iron promotes lipid peroxidation and T-cells’ ferroptosis. Upon stimulation, we detected changes in the balance of ferroptosis-suppressive proteins, including decrease of GPX4. Subsequently, we identified GPX4 as a master regulator orchestrating T/CAR-T-cells’ sensitivity to ferroptosis and observed that GPX4 inhibitors impair CAR-T cells’ antitumor functions. Our study demonstrated differential GPX4 expression and diverse susceptibility to ferroptosis between CD4⁺ and CD8⁺ T cells. Among analyzed subsets of naïve, central memory (CM), effector memory (EM), and terminally differentiated effector memory (TEMRA), CD8⁺ EM and CD8⁺ TEMRA cells exhibited the highest sensitivity to ferroptosis. We also showed that ferroptosis limited the anti-tumor efficacy of CAR-T cells, while ferroptosis inhibition improved their therapeutic effect, both in vitro and in vivo. Our findings are not only important to understand vulnerabilities of CAR-T cells but may also hold particular significance for their therapeutic development. In this context, future anticancer therapies should be carefully designed to selectively induce the ferroptosis of tumor cells without impeding cytotoxic cells’ antitumor efficacy. Additionally, we postulate that promoting less differentiated phenotype of CAR-T cells should be exploited therapeutically to create CAR-T products characterized by decreased sensitivity to ferroptosis within tumor microenvironment.